Fundamental motor skills of Czech children at the end of the preschool period - Kokštejn, Jakub; Musálek, Martin; Šťastný, Petr; Golas, Artur (Acta Gymnica, 2017)
Background: Achievement of a sufficient fundamental motor skills (FMS) level by the end of the preschool period is an important premise for the later participation of children in many sports activities. However, only a few studies have focused on the assessment of motor proficiency before entrance to elementary school in the population of preschool children in the Czech Republic. Objective: The aim of this study was to assess the FMS of Czech boys and girls at the end of the preschool period. Methods: The Movement Assessment Battery for Children-second version (MABC-2) was used to assess the motor performance of the children in different domains, i.e., manual dexterity, aiming and catching, and balance. The research sample consisted of 121 children (age 6.5 ± 0.3 years, 61 boys and 60 girls). Results: According to the total test score performance on MABC-2, we found 2.5% of children with severe motor difficulties indicating the possible presence of Developmental Coordination Disorder and 10.7% of children with a risk of motor difficulties. In total, 64% of boys and 81.6% of girls had an MABC-2 score in the 50th percentile or lower. With respect to gender differences, boys outperformed girls in aiming and catching skills (p < .001; d = 1.10). Moreover, the girls' score in the 25th percentile indicated a low level of aiming and catching skills. Despite significantly better results for boys in one manual dexterity test item, and for girls in one manual dexterity and balance test item, there were no significant gender differences in overall manual dexterity and balance subtests. Conclusion: With the preschool years being a key developmental stage for the acquisition and development of FMS, the findings of low level of FMS in most of children and gender differences in aiming and catching skills highlight the need for improvements in motor competency. An effort should be made, especially for preschool girls, to stimulate the improvement of aiming and catching skills.
Keywords: motor development; preschool age; gender differences; MABC-2